Pengaruh Terapi Mewarnai Gambar Terhadap Kecemasan Anak Usia Pra Sekolah - Molintao, Winarsi; Legi, Julita; Adrian, Ivilia (JURNAL ILMIAH KESEHATAN MANADO, 2025)
Every child who is hospitalized will experience feelings of insecurity such as unfamiliar surroundings, separation from parents, lack of information, loss of freedom and independence. Even though the child is sick, the need to play remains. The purpose of this study was to determine the effect of coloring therapy on the anxiety of preschool children in the upper Edelweys room of Bhayangkara Hospital Level III Manado. This type of research uses a "one group pre-test-post-test design" design. The population in this study were 59 preschool children. The sample in this study was 16 children. The results of this study indicate that from the samples studied, there is an Effect of Coloring Therapy on the Anxiety of Pre-School Children, obtained a value of ρ = 0.000 <α = 0.05. There is an Effect of Coloring Therapy on the Anxiety of Pre-School Children in the Upper Edelweys Room of Bhayangkara Hospital Level III Manado. The results of this study are expected to be input for research locations, especially for mothers and nurses in dealing with children who are being treated in hospitals so that they can provide play therapy to children so that they can reduce anxiety in children due to hospitalization.